Psychosocial frameworks of the argumentative discourse in the migratory ecology towards Chile - Noemi, Cristian (2023)
In recent years, the trend of subcontinental migration to Chile – due to its economic dynamism – has reached figures never before recorded and modified the demographic context of the country. In this sense, the work analyzes the psychosocial representations of the speakers of this new discursive ecology and its relationship with the flow of argumentative discursive information that they generate. The results show that Chilean speakers have mostly activated certain psychosocial frameworks and, consequently, generate argumentative sequences with a point of view against with preference for ad misericordiam arguments. Immigrant speakers have less activation of psychosocial frameworks and, consequently, generate a point of view in favor based on arguments of justice.